2020
DOI: 10.1021/acs.jafc.0c00138
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin-Caged Compounds of 1-Naphthaleneacetic Acid as Light-Responsive Controlled-Release Plant Root Stimulators

Abstract: Six coumarin-caged compounds of 1-naphthaleneacetic acid (NAA) comprising different substituents on the coumarin moiety were synthesized and evaluated for their photophysical and chemical properties as light-responsive controlled-release plant root stimulators. The 1H NMR and HPLC techniques were used to verify the release of NAA from the caged compounds. After irradiation at 365 nm, the caged compounds exhibited the fastest release rate at t 1/2 of 6.7 days and the slowest release rate at t 1/2 of 73.7 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…The developed formulation was only effective for insects with transparent body structure due to the relatively short absorption wavelength of the insecticide. Very recently, coumarin-caged compounds of 1-naphthaleneacetic acid have been synthesized and used as light-responsive plant root stimulators …”
Section: Safe Pesticide Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The developed formulation was only effective for insects with transparent body structure due to the relatively short absorption wavelength of the insecticide. Very recently, coumarin-caged compounds of 1-naphthaleneacetic acid have been synthesized and used as light-responsive plant root stimulators …”
Section: Safe Pesticide Applicationmentioning
confidence: 99%
“…Very recently, coumarin-caged compounds of 1-naphthaleneacetic acid have been synthesized and used as light-responsive plant root stimulators. 100 In general, research related to light-responsive pesticide nanoformulations has been rarely reported. The currently developed mesoporous silica-based pesticide nanoformulations primarily feature good photostability to protect the pesticides from photodegradation, rather than the light-responsive characteristics.…”
Section: ■ Safe Pesticide Applicationmentioning
confidence: 99%
“…In the latest publication on caged-auxins, Keawchangwat presented the synthesis of caged NAA with coumarin-based photoremovable protecting groups (Figure , 6a – 6f ) . Prepared compounds with hydroxy-, chloro-, and methylenedioxy substituents on the coumarin phenyl moiety showed strong fluorescence with an emission wavelength maxima between 425 and 492 nm.…”
Section: Caged Phytohormonesmentioning
confidence: 99%
“…In the latest publication on caged-auxins, Keawchangwat presented the synthesis of caged NAA with coumarin-based photoremovable protecting groups (Figure 6, 6a−6f). 93 Prepared compounds with hydroxy-, chloro-, and methylene-dioxy substituents on the coumarin phenyl moiety showed strong fluorescence with an emission wavelength maxima between 425 and 492 nm. In vitro photolysis of compounds 6a−6f in 1 M HEPES/MeOH media (20:80) exposed to 365 nm UV light (6 W) resulted in a progressive release of NAA, being the most effective and rapid for 6e (10th day 60% release of NAA) followed by 6a.…”
Section: Caged Phytohormonesmentioning
confidence: 99%
“…As an important class of allelochemicals, coumarin compounds have allelopathic effects on many plants 5,6 . which include damage to the cell membrane, abnormalities in hormone levels, and changes in plant cell division and photosynthesis 7–9 .…”
Section: Introductionmentioning
confidence: 99%